DETECTION OF AMP-C BETA-LACTAMASES IN URINARY ISOLATES OF ESCHERICHIA COLI THROUGH VARIOUS PHENOTYPIC METHODS: AMP C Beta-Lactamases in Urinary Isolates of Escherichia Coli - Fahim, Qanita; Khalid, Ayesha; Hameed, Fatima; Anwar, Saeed (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the prevalence of Amp C beta lactamases in urinary isolates of Escherichia coli (E. coli),and to evaluate and compare different phenotypic methods for its detection in a cost effective way.Study Design: Descriptive study.Place and Duration of Study: Department of Microbiology, Combined Military Hospital Lahore Pakistan, fromJan 2016 to Jun 2016.Material and Methods: Modified Three Dimensional Test (M3DT) taken as Gold standard, Modified Hodge Test(MHT) (Cefoxitin), Nitrocephin test and three screening strategies for the detection of Amp C Beta-lactamaseswere tested on urinary isolates of E. coli collected during a period of 06 months.Results: Modified Hodge Test, was found to be simple, highly specific and sensitive in detecting these enzymeproducers. Collectively these tests detected 45.07% of E. coli to be Amp C producers.Conclusion: Each of the three tests can be used as an acceptable phenotypic confirmatory tool when Amp C productionin E. coli is suspected.